Pusat Payudara UIAM dan Program Subsidi Mamogram LPPKN di Pusat Payudara UIAM (IIUM Breast Centre): 2007-2011 - Che Mohamed, Siti Kamariah (2012)
The aim of the lecture is to promote IIUM Breast Centre as one of the accredited centres for breast cancer screening, including LPPKN mammogram subsidy programme. The result of an audit of LPPKN mammogram subsidy programme done at IIUM Breast Centre from 2007 till 2011 was also presented.